Law and Freedom as a project - Fernández Sessarego, Carlos (2016)
This article reflects on the figure of “life project”, focusing on its philosophical foundations, and its relation to freedom and the person as a “freedom being”. To do this, the author explains the different definitions elaborated regarding thehuman being as a subject of Law, and the notions of “freedom as a project” that have been outlined by philosophers like Jean Paul Sartre, Xavier Zubiri, Julián Marías, Karl Jaspers, among others.Also, the history of the concept of “freedom as a life project” is developed, as well as the requirements for a project of life, the means for choosing the project life, the time when a life project is chosen, the difference between an authentic life project and an inauthentic one, and the notions of a life project “substitute” and an “alternative” one. Finally, the difference between will and freedom, life project and free development of personality, and some preliminary concepts for the current protection and diffusion of the “damage to a life project” are established.